Exploring the relation between methylxanthines and plasma lipids in two population-based studies. (30th September 2020) - Petrovic, D; Pruijm, M; Ponte, B; Ackermann, D; Ehret, G; Zhang, Z; Thijs, L; Staessen, J; Bochud, M; Guessous, I
Abstract: Background: Chronic intake of caffeinated beverages might be associated with plasma lipids via disturbed lipid metabolism. Previous investigations have been limited by the use of self-reported caffeine intake instead of measured caffeine, whereas the associations between plasma lipids and other methylxanthines (paraxanthine, theobromine, theophylline) are unknown. Here, we investigated the associations of plasma lipids with caffeine and its metabolites in plasma and urine in two European populations. Methods: Individuals were selected from the general population of North Belgium (FLEMENGHO) and Switzerland (SKIPOGH). Total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides were measured in plasma using standard enzymatic methods. Plasma and 24h urinary caffeine, paraxanthine, theophylline, and theobromine excretions were measured using ultra-high performance liquid chromatography tandem mass spectrometry. We used mixed models to explore the associations of methylxanthines with plasma lipids while adjusting for major confounders. Results: Overall, 1946 FLEMENGHO participants (911 men, age 45.9±15.2 years) and 990 SKIPOGH participants (467 men, age 47.1±17.3 years) were included. Mean plasma total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides in FLEMENGHO/SKIPOGH were 5.37/5.06, 3.12/3.12, 1.43/1.50, and 2.4/1.02 mmol/L. In both cohorts, adjusted mean total cholesterol, LDL cholesterol, and HDL cholesterol, increased with quartile of plasma caffeine, with stronger associations in men. Similar positive associations were observed for paraxanthine and theophylline. Similar associations were observed using 24h urine excretions in SKIPOGH. Conclusions: Plasma and urinary caffeine, paraxanthine, and theophylline were positively associated with plasma lipids in men, whereas there were fewer meaningful associations in women. The increase in plasma lipids might mitigate the overall beneficial impact of caffeinated beverages on health. Key messages: Caffeine constitutes one of the most widely consumed biological active substances. Plasma concentration and urinary excretion of caffeine and its derived metabolites is positively associated with plasma lipids.